ANALISA TEKNIS DAN EKONOMIS PERHITUNGAN KEBUTUHAN MATERIAL TERHADAP REALISASI PAINTING PADA PROSES PEMBANGUNAN BLOCK 211 (PS) DAN BLOCK 221 (PS) KAPAL LD - Pratama, Andhika Rafly; Basuki, Minto (UNIMAR AMNI Semarang, 2025)
LD ship is one of the new construction ships produced at PT. PAL Indonesia. The painting process is a process that needs to be considered in ship construction. Because the painting process is an important activity in protecting the steel surface from corrosion and increasing the life of the steel structure. However, in its implementation, there is often a discrepancy between the calculation of theoretical paint material requirements and the amount of material used actually. This study aims to analyze the comparison of the difference between the planned paint material requirements and the realization in the field, as well as to evaluate the technical and economic aspects of the construction of block 211 (P/S) and block 221 (P/S) ships (LD) at PT. PAL Indonesia. However, in practice, it is often found that the value of the planned material requirements in the system is not in line with the actual conditions in the field, especially regarding material requirements and costs. From the results of the case study, the results of the difference in painting material requirements between the estimate and the actual in the field are the types of Jotacote N10 paint, Alu Grey, a difference of 5 pails was obtained, and the types of Jotacote N10 paint, ALRT Red, Hardtop XP, Red (RAL 3001), Safeguard Universal Es, Plum, and Seamate NB, Light Red, each of which had a difference of 1 pail. The total man-hours were 684,255 JO with a total labor cost of Rp. 15,540,000 for 21 days.